I need to find such F, so that for any M $FM = MF$. I can't figure out, how to bring this equation to the form like this: $F = TF$, so that I could just apply Y combinator


We want a definition like:

$F = \lambda x.xF$

Instead of using $Y$, we can use $R=\lambda x.xx$ for recursion.

$F = R(\lambda fM.M(Rf))$


$$ FM = R(\lambda fM.M(Rf)) \\ = (\lambda x.xx)(\lambda fM.M(Rf))M \\ = (\lambda fM.M(Rf))(\lambda fM.M(Rf))M \\ = M(R(\lambda fM.M(Rf))) \\ = MF $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.